2019
DOI: 10.1242/jcs.227728
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-based modifications in endothelial cell–cell contact and inflammation

Abstract: Endothelial cell-cell contacts are essential for vascular integrity and physiology, protecting tissues and organs from edema and uncontrolled invasion of inflammatory cells. The vascular endothelial barrier is dynamic, but its integrity is preserved through a tight control at different levels. Inflammatory cytokines and G-protein-coupled receptor agonists, such as histamine, reduce endothelial integrity and increase vascular leakage. This is due to elevated myosin-based contractility, in conjunction with phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 146 publications
(178 reference statements)
0
18
0
Order By: Relevance
“…Wong et al found that the 44-amino-acid peptide in the second extracellular loop of occludin had no effect on the expression level of ZO-1, ZO-2, or cingulin in the Xenopus kidney epithelial cell line A6 [21]. Therefore, in the present study, only the dynamic expression of occludin was quantitatively analyzed when investigating the mechanism underlying the destruction and recovery of TJ Manuscript to be reviewed protein degradation [32]. Occludin phosphorylation and ubiquitination regulate TJ [33].…”
Section: Discussionmentioning
confidence: 87%
“…Wong et al found that the 44-amino-acid peptide in the second extracellular loop of occludin had no effect on the expression level of ZO-1, ZO-2, or cingulin in the Xenopus kidney epithelial cell line A6 [21]. Therefore, in the present study, only the dynamic expression of occludin was quantitatively analyzed when investigating the mechanism underlying the destruction and recovery of TJ Manuscript to be reviewed protein degradation [32]. Occludin phosphorylation and ubiquitination regulate TJ [33].…”
Section: Discussionmentioning
confidence: 87%
“…Suggesting defective junctional protein degradation and turnover in autophagy impaired ECs, these findings are in agreement with the targeting of junctional components by autophagy mechanisms reported in other cell types ( Bejarano et al., 2012 ; Nighot et al., 2015 ; Wang et al., 2014 ). Regulated by a plethora of post-translational modifications, including phosphorylation and ubiquitination, vesicular trafficking of EC junctional components dictates their cellular localization and functional properties ( Majolée et al., 2019 ; Wessel et al., 2014 ). Notably, both phosphorylation and ubiquitination act as molecular signals that can target specific pools of proteins to autophagic compartments ( Bejarano et al., 2012 ; Levine and Kroemer, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are three possible reasons for the decrease in protein expression. The first reason is protein degradation (Majolee, Kovacevic & Hordijk, 2019). Occludin phosphorylation and ubiquitination regulate TJ (Murakami, Felinski & Antonetti, 2009).…”
Section: Discussionmentioning
confidence: 99%